Clinical Profile and Status of Blood Glucose in Asphyxiated Newborns (TAJ: Journal of Teachers Association, 2019)
Perinatal asphyxia will be defined as 1-minute apgar-score of 6 or less. Fifty cases and fifty control was observed in this study. The main clinical presentation were convulsion, respiratory distress, apnea, excess crying etc. From all babies blood glucose was done by colorimetric methods. In asphyxiated newborns mean (± SEM) serum glucose level was 75.26 mg/dl which was significantly lower than the mean serum glucose level of control (± SEM) 77.64 mg/dl. Hypoglycaemia asphyxiated newborn were 42%. In convulsive infants 60% were associated with hypoglycaemia. So, the study shows that hypoglycaemia occurs frequently in asphyxiated newborns and earlier appropriate treatment can reduce morbidity and mortality significantly.TAJ 2010; 23(1): 55-58